Regular changes in foot strike pattern during prolonged downhill running do not influence neuromuscular, energetics, or biomechanical parameters - Vernillo, G.; Aguiar, M.; Savoldelli, A.; Martinez, A.; Giandolini, M.; Horvais, N.; Edwards, W. B.; Millet, G. Y. (European Journal of Sport Science, 2020)
Research has suggested that a high variability in foot strike pattern during downhill running is associated with lower neuromuscular fatigue of the plantar flexors (PF). Given the popularity of trail running, we designed an intervention study to investigate whether a strategy with regular changes in foot strike pattern during downhill running could reduce the extent of fatigue on neuromuscular, energetics and biomechanical parameters as well as increase an uphill time-to-exhaustion trial (TTE) performance. Fourteen experienced trail runners completed two interventional conditions (separated by 15 days) in a pseudo-randomised and counter-balanced order that consisted of 2.5-h of treadmill graded running with (switch condition) or without (control condition) a change between fore- and rear-foot strike pattern every 30 s during the downhill sections. Pre and Post, neuromuscular tests were performed to assess PF central and peripheral fatigue. Energy cost of running was assessed using an indirect calorimetry system and biomechanical gait parameters were acquired with an instrumented treadmill. TTE was performed after both the graded running conditions. There were not significant condition × time interactions (p = .085) for any of the variables considered, and TTE was not different between the two conditions (p = .755). A deliberate strategy to alternate between foot strike patterns did not reduce the extent of fatigue during prolonged graded running. We suggest that it is not the ability to switch between foot strike patterns that minimises fatigue; rather the ability to adapt foot strike pattern to the terrain and therefore a better running technique.